Mayo Clinic strategies to reduce burnout : 12 actions to create the ideal workplace - Swensen, Stephen J.; Shanafelt, Tait D.; Mayo Clinic (New York, NY : Oxford University Press, 2020)
Many believe burnout of health care professionals to be the result of individual weakness when, in fact, burnout is primarily the result of health care systems that take emotionally healthy, altruistic people and methodically squeeze the vitality and passion out of them. In this work, we tell the story of burnout of health care professionals, although we chose not to dwell on negative aspects of the story. Instead, we emphasize nurturing positivity and a hope for professional fulfillment, well-being, and joy and meaning in work.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 4, 2020).
Keywords: Medical personnel -- Mental health; Stress management; Burn out (Psychology); Morale